2022
DOI: 10.1063/5.0096667
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-frequency broadband characteristics of stepwise radial metamaterials

Abstract: A new type of stepwise radial metamaterial (SRM) with ultralow-frequency and broadband characteristics is proposed in this study. In contrast to the traditional radial metamaterial (TRM), the proposed structure is periodically arranged in a stepwise shape along the radial direction. The propagation characteristics of Lamb waves in the SRM were investigated using the finite element method. For the numerical analysis, the degeneracy between the bands of the SRM was separated, resulting in the opening of the band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that even though the above calculation of the energy band curve of the SR-ABH is based on the ideal structure with the infinite period, it is unrealistic to apply the wireless period in practice. Thus, it is necessary to use the elastic wave transmission properties of the finite period structure to verify the shielding characteristics of the designed structure with respect to the elastic wave [24]. In particular, the displacement excitation u input at the SR-ABH boundary can be assumed, and the displacement output u output can be recorded at the truncation of the SR-ABH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that even though the above calculation of the energy band curve of the SR-ABH is based on the ideal structure with the infinite period, it is unrealistic to apply the wireless period in practice. Thus, it is necessary to use the elastic wave transmission properties of the finite period structure to verify the shielding characteristics of the designed structure with respect to the elastic wave [24]. In particular, the displacement excitation u input at the SR-ABH boundary can be assumed, and the displacement output u output can be recorded at the truncation of the SR-ABH.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al [23] designed a composite radial metamaterial whose band gap characteristics exceeded traditional metamaterials due to the coupling effect inside the proposed structure. Li et al [24] developed a stepped radial metamaterial, which opened the local resonance and Bragg scattering band gap by introducing a gradient array, enhancing the ultra-low frequency broadband characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…( 6) in Eqs. ( 7) and (8). As substantiated in [7] and [13], the resulting determinant is a fourth-order polynomial in Λ:…”
Section: Polar Coordinatesmentioning
confidence: 86%
“…In all these cases, radial periodicity can be utilised to reduce vibration transmission, and the periodic inserts can function as a vibroacoustic filter when the dominant excitation frequency falls within a stopband. The use of radial periodicity for vibration reduction was, for example, investigated in [8] where it was shown that a periodic structure, arranged in a stepwise shape along the radial direction, was able to attenuate vibration due to its low-frequency bandgap characteristics. Radial periodic structures have also been shown to be effective in protecting constructions from seismic waves; as an example, in [9], a new type of seismic metamaterial with radial periodicity was studied, demonstrating its effectiveness, compared to traditional seismic metamaterials, in attenuating seismic Lamb and surface waves.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a finite-period structure, it is necessary to calculate the transmittance to describe its transmission characteristics. The transmittance is determined by applying acceleration excitation along the Y-direction at one end of the finite-period structure and simultaneously recording the acceleration response generated at the other end [45]. The transmittance is calculated as follows:…”
Section: Theoretical Modeling For the Vibroacoustic Characteristicmentioning
confidence: 99%